Comparison of toxicogenic and immunosuppressive capacity of Aspergillus fumigatus strains isolated from clinical and corn silage samples - Dogi, Cecilia Ana (2015)
Aims: To compare clinical and environmental Aspergillus fumigatus strains on their toxicogenic and immunosuppressive capacity. Methods and Results: A total of 51 strains of A. fumigatus isolated from clinical and corn silage samples were assayed. All A. fumigatus strains were assayed for gliotoxin production, therefore strains with different gliotoxin capacities and isolated from different sources were selected and assayed for their effects on bovine macrophages and lymphocytes. Spore diffusates (SDs) obtained from all A. fumigatus strains were able to inhibit macrophage phagocytosys, regardless of their gliotoxin production capacity. However, most but not all strains were able to inhibit bactericidal activity. SDs from all A. fumigatus strains reduced lymphocytes viability. The heat treatment was not always able to inhibit the negative effect on immune cells. Conclusions: There was no difference between clinical and environmental isolates in their toxicogenic and immunosuppressive capacity. Gliotoxin would not be responsible for the immunosuppressive activity observed by the assayed A. fumigatus strains. However, gliotoxin could be present in the SD, together with some other substances. Significance and Impact of the Study: The results obtained suggest that any environmental strain of A. fumigatus is a putative infectious strain. Prevention measures should be applied to control environmental Aspergillus conidia.